Prevalence of violence in the population of the canton of Tibás: January 2012 to July, 2014 - Araya Solís, Mauren (2015)
Introduction: The objective of this research is to identify the prevalence of violence in the population of the Cantón of Tibás, January 2012 to July 2014. The violence involves possibility of injury or damage itself, which negatively affects the health of people either as a group or as individuals, why it is essential to identify and describe its manifestations in the community, in order to take concrete measures against it, reduce its impact and improve the health of people. Methodology: The study is a descriptive epidemiological investigation and transverse type, based on data collected in the area of Health Governing Canton Tibás by ballot notifiable VE-01. Results: It was determined that violence is a situation that affects mostly children aged 0-9 years, and most common type is the neglect or abandonment. As for the worst affected areas, Cinco Esquinas stands out, followed by León XIII, also the female gender is most affected, which is consistent with the literature reviewed. Conclusion: We conclude that violence is a public health problem, a phenomenon with multiple implications and within the most vulnerable women, the elderly and children are, without forgetting that all people are exposed suffer some kind of violence.